Foreign experience study of personality traits effective manager - Кот, Г.М.; Пилипчук, О.Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
The article represents requirements to managers and analyses types of character need for effective work. There is also important information about the accent on individual work with personal in the article.